Qiraat mutawatir dan kesannya kepada hukum fiqh: Kajian pengetahuan dan pendedahan dalam kalangan ilmuwan Islam di Terengganu / Mohd A'tarahim Mohd Razali - Mohd A'tarahim, Mohd Razali (2017)
Qiraat Mutawatir is among one of the disciplines in the study of Qur’an. It is also deeply related to other Islamic disciplines. In Fiqh (Islamic jurisprudence), Qiraat has brought significant impact among the Fuqaha’ (jurists) in shaping and determining matters related to Islamic Fiqh. Despite its importance, it is found that many Islamic scholars have overlooked the influence of Qiraat in Fiqh and thus lack the ability to elucidate several vague and ambiguous matters of Qiraat and its relation to Fiqh. The objective of this study is therefore to analyse the depth of familiarity and knowledge that Islamic scholars in Terengganu have on the impact of Qiraat in Fiqh. This study is both qualitative and quantitative. Data was gathered from library research, observations, interviews and surveys. These were analysed descriptively, inductively, deductively and comparatively so as to offer several important solutions that could promote Qiraat knowledge holistically. The results show that Qiraat is one of the main sources of determining Fiqh. It has also significantly shaped the discussions among Islamic scholars in Qiraat, Fiqh and their respective madzhabs. The findings also reveal the lack of knowledge and exposure that Islamic scholars in Terengganu have regarding the relationship of Qiraat and Fiqh. The implication of this study reveals that there is a need to improve the level of knowledge among Islamic scholars in Terengganu regarding the relationship and the impact of Qiraat on Fiqh. This should be accomplished systematically and continuously in the future.